First historical checklist of spiders (Arachnida: Araneae) from Morocco, between 1840–2024 - Benhalima, Souâd; Bosmans, Robert (Zootaxa, 2024)
The checklist of Spiders (Araneae) of Morocco is presented for the first time, based on about two centuries of arid research (between 1840 and 2024), including an extensisve bibliographic study. This updated list includes a total of 549 species belonging to 225 genera and 46 families. A bibliographic review, as complete as possible, was compiled which to date includes 172 references, providing a database available for the first time and accessible for any future research on Moroccan spiders. This work is also the first step towards a catalog and an Atlas of this group of arachnids, which is currently being compiled and is the first of its kind in Morocco and even North Africa.